Stereotactic Radiosurgery for Hemorrhagic Symptomatic Cerebral Cavernous Malformations: An International Multicenter Study. (16th November 2020) - Kano, Hideyuki; Jacobs, Rachel; Yang, Huai-Che; Lee, Cheng-Chia "Justin"; Nabeel, Ahmed; Abdelkarim, Khaled; Emad, Reem; El-Shehaby, Amr; Reda, Wael; Tawadros, Sameh; Khalil, Piettar; Liscak, Roman; et al.
Abstract: INTRODUCTION: Stereotactic radiosurgery has been used for treating cavernous malformation. METHODS: Between 1988 and 2018, Gamma Knife® SRS was performed in 762 evaluable patients with symptomatic CCMs There were 262 (34%) CCM in the brainstem, 148 (19%) in basal ganglia or thalamus, and 372 (49%) in lobar locations. Most patients had experienced 2 or more hemorrhages associated with new neurological deficits. The median CM volume was 1.2 cm 3 (range, 0.01-28.9), and the median margin dose was 14.0 Gy. RESULTS: After SRS, 158 patients (21%) had an imaging confirmed new hemorrhage at a median follow-up of 49 months. The hemorrhage-free survival after SRS for CCMs was 91% at 1 year, 86% at 3 years, and 81% at 5 years. The annual hemorrhage rate was 5.6% before and 0.3% after SRS. In univariate analysis, CM volume, brainstem or basal ganglia or thalamus, and increased number of hemorrhages before SRS was significantly associated with a higher rate of rehemorrhage after SRS. In multivariate analysis, number of prior hemorrhages ( P < . 0001, HR = 1.31, 95% CI: 1.19-1.47) and lower margin dose ( P = . 03, HR = 0.91, 95%CI: 0.85-0.97) were significant. Symptomatic adverse radiation effects (ARE) developed in 27 patients (3.5%). CONCLUSION: Patients with an increased rate of hemorrhage before SRS had an increased risk of rehemorrhage. SRS has proven especially valuable in patients with deep seated, smaller CCM, and those with a smaller number of prior bleeds.